Demetris Z. Pierides collection of contemporary Greek painting and engraving. - Eliopoulou-Rogan, Dora (Athene : [s.n.], 1982)
Giallinas, Angelos ; Christou Kassialos, Michael ; Lytras, Nicolaos ; Maleas, Constantinos ; Bouzianis, Georgios ; Economou, Michael ; Steris, Gerassimos ; Gounaropoulos, Georgios ; Byzantios, Pericles ; Papaloukas, Spyros ; Vassiliou, Spyros ; Georgiou, George P. ; Diamantis, Adamantios ; Hadjikyriakos-Ghikas, Nikos ; Kontopoulos, Alecos ; Spyropoulos, Jannis ; Nikolaou, Nikos ; Tsarouchis, Yannis ; Mavroides, Georgios ; Moralis, Yannis ; Tsingos, Thanos ; Sikeliotis, Giorgos ; Varlamos, Giorgis ; Tetsis, Panagiotis ; Kokkinides, Demosthenis ; Manousakis, Georgios ; Dekoulakos, Elias ; Tsoclis, Costas ; Paniaras, Costas ; Pavlos (Pavlos Dionyssopoulos) ; Karas, Christos ; Kessanlis, Nikos ; Mytaras, Dimitris ; Metaxas, Stamatis-Panagiotis ; Droungas, Achilles ; Fassianos, Alekos ; Mytara, Hariclea ; Karavousis, Sarantis ; Theophylaktopoulos, Makis ; Papanelopoulos, Yannis ; Makroulakis, Michalis ; Manolidis, Theodoros ; Zouni, Opy ; Galanis, Demetris ; Kefallinos, Ioannis ; Ventouras, Nikolaos ; Kanthos, Telemachos ; Alevizos, Tassos ; Grammatopoulos, Constantin P. ; Katraki, Vasso
Engels & Grieks
boek